Treatment outcomes of extrapulmonary tuberculosis in Bahawalpur, Pakistan; a record review - Atif, Muhammad; Fatima, Razia; Ahmad, Nafees; Babar, Zaheer-Ud-Din (Journal of pharmaceutical policy and practice, 2020)
There is limited published data form Pakistan on treatment success rate among extrapulmonary tuberculosis (EPTB) patients. The aim of this study was to assess clinical form, treatment outcomes, and identify the factors associated with unfavorable treatment outcome among EPTB patients. A retrospective study was conducted at the Chest Disease Unit of the Bahawal Victoria Hospital, Pakistan. Medical records of EPTB patients, registered at the study site from January 1, 2015 to September 30, 2017, were reviewed to obtain the data. Final treatment outcomes among EPTB patients were evaluated in accordance with the standard Word Health Organization (WHO) criteria. Multivariate binary logistic regression analysis was used to identify the factors associated with unfavorable treatment outcome. A total of 651 EPTB patients were included in the study. Highest proportion of patients had pleural TB ( = 217, 33.3%). Out of the total 651 patients, 463 (71.1%) successfully completed the treatment. Among 177 (27.2%) patients with unfavorable treatment outcome, 10 (1.5%) died, while 165 (25.4%) lost to follow-up the treatment. Lymph node TB (AOR 0.65, 95% CI 0.422, 0.989) and meningeal TB (AOR 2.1, 95% CI 1.065, 4.144) were significantly associated with unfavorable treatment outcome. The treatment success (favorable outcome) rate among EPTB patients was less than the target (i.e., ≥ 90%) set by the WHO. Highest proportion of patients lost to follow-up during the treatment.